Expression of Neurofilament Subunits at Neocortical Glutamatergic and GABAergic Synapses - Luca Bragina; Luca Bragina; Fiorenzo Conti; Fiorenzo Conti (Frontiers Media S.A., 2018)
Neurofilaments (NFs) are neuron-specific heteropolymers that have long been considered as structural proteins. However, it has recently been documented that they may play a functional role at synapses. Indeed, the four NF subunits-NFL, NFM, NFH and α-internexin-are integral components of synapses in the striatum and hippocampus, since their elimination disrupts synaptic plasticity and impairs social memory, an observation that might have important implications for some neuropsychiatric diseases. Here, we studied NFs localization in VGLUT1-, VGLUT2-, VGAT-, PSD-95- and gephyrin-positive (+) puncta, and in glutamatergic and GABAergic synapses in the cerebral cortex of adult rats. Synapses were identified by pre- and postsynaptic markers: glutamatergic synapses by VGLUT1+ or VGLUT2+ puncta contacting PSD-95+ puncta; and GABAergic synapses by VGAT+ puncta contacting gephyrin+ puncta. In VGLUT1 glutamatergic synapses NF showed a greater expression in the compartment labeled by postsynaptic markers (20%-30%) than in those labeled by presynaptic markers (10%-20%), whereas in GABAergic synapses a similar expression was detected in both compartments (20%-30%). Moreover, NF expression was higher in the GABAergic (20%-30%) than in the glutamatergic (10%-15%) compartments labeled by presynaptic markers. Finally, a higher colocalization of VGLUT1+, VGLUT2+ and VGAT+ puncta with NFs was seen when presynaptic puncta contacted elements labeled by postsynaptic markers. These findings show that the four NF subunits are expressed at some neocortical synapses, and contribute to glutamatergic and GABAergic synapse heterogeneity.